2022
DOI: 10.1093/jcde/qwac114
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pairings of colors and materials of furnishings in interior design with a data-driven framework

Abstract: Color–material furnishing pairing is known as a “black-box” for interior designers. The overall atmosphere of a space can be changed by modifying furnishing combinations, for example, to express modern or classic styles. Designers carefully choose pairings of colors and materials that fit their intended interior design styles based on experience and knowledge. However, no specific principles or rules have yet been established. Therefore, this study aims to derive a furnishing pairing principle based on a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Park et al proposed a framework based on object detection and so on to derive furniture pairing principles. These experiments confirmed that images with high fidelity values matched existing style descriptions, proving that this framework could be used for indoor style image retrieval [12]. Solah et al proposed an automatic adjustment of the texture and color of virtual indoor scene objects to match target emotions.…”
Section: Related Workmentioning
confidence: 61%
“…Park et al proposed a framework based on object detection and so on to derive furniture pairing principles. These experiments confirmed that images with high fidelity values matched existing style descriptions, proving that this framework could be used for indoor style image retrieval [12]. Solah et al proposed an automatic adjustment of the texture and color of virtual indoor scene objects to match target emotions.…”
Section: Related Workmentioning
confidence: 61%
“…Another significant challenge in interior design is the attainment of aesthetically pleasing designs 1 , 4 . Interior designers must factor in elements such as spatial layout, color harmony, material choice, furniture arrangement, and lighting design, among others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, material mapping is assigned to the 3D model, lighting is arranged for the space, and renderings are obtained. Finally, the customer determines whether the design is suitable by observing the renderings [5]. The linear workflow requires designers to design step by step.…”
Section: Conventional Interior Design Processmentioning
confidence: 99%
“…Existing design automation mainly focuses on a particular process in the design, but fewer studies focus on end-to-end design [4,5]. This study achieves end-to-end generation of interior design by building a text-to-image diffusion model, thereby improving design efficiency and addressing the lack of creativity.…”
Section: Conventional Interior Design Processmentioning
confidence: 99%
See 1 more Smart Citation